2001
DOI: 10.1097/00005537-200110000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Concentration of Epinephrine for Vasoconstriction in Ear Surgery

Abstract: One percent lidocaine control exhibited the expected initial vasodilatory effect for approximately 5 minutes. In this experimental model, using a lower concentration of 1:200,000 epinephrine would supply equivalent vasoconstriction in the ear compared with higher concentrations, thus reducing the possible systemic toxicity and related morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 19 publications
2
34
0
1
Order By: Relevance
“…14 To prevent side effects, it is important to strictly limit the dose of epinephrine, and the optimal concentration of epinephrine may vary based on the anesthetic agent and the site of injection. 12,15,16 Epinephrine, a catecholamine, itself at 1:100,000 induced a transient and partial block of infiltrative cutaneous analgesia in rats. 17 We suggested that the addition of epinephrine could influence bupivacaine, DM, 3MM, or DX cutaneous analgesic effect in rats.…”
mentioning
confidence: 99%
“…14 To prevent side effects, it is important to strictly limit the dose of epinephrine, and the optimal concentration of epinephrine may vary based on the anesthetic agent and the site of injection. 12,15,16 Epinephrine, a catecholamine, itself at 1:100,000 induced a transient and partial block of infiltrative cutaneous analgesia in rats. 17 We suggested that the addition of epinephrine could influence bupivacaine, DM, 3MM, or DX cutaneous analgesic effect in rats.…”
mentioning
confidence: 99%
“…For this reason, the 32 mixtures of epinephrine and the local anesthetics (e.g., long-lasting 33 local anesthetic bupivacaine) were used to extend the duration of 34 central and peripheral neuraxial blockades [21] and were often 35 performed during dental, surgical, or medical practices [22,23]. In 36 order to prevent side effects, it is important to select the 37 appropriate dose of epinephrine seriously though the favorable 38 epinephrine dose may vary according to the local anesthetics and 39 their injection sites [21,24,25]. 40 It has been accepted that epinephrine as a vasoconstrictor helps 41 attenuating local blood loss [26], and therefore prolongs the duration 42 of action of local anesthetics [21].…”
Section: Q3mentioning
confidence: 99%
“…Duration (full recovery time) of drug action (n = 8 at each testing point) as an infiltrative anesthetic at 50% effective doses (ED 50 ), ED25 , and ED 75 . Data are mean AE SEM.…”
mentioning
confidence: 99%
“…It has been shown that epinephrine (1:200,000; 5 μg/mL) combined with lidocaine or bupivacaine was as effective as higher doses at causing vasoconstriction and prolonging analgesia in human skin (Liu et al, 1995). In addition, epinephrine (5 μg/mL) added to lidocaine 1% was as effective as higher concentrations of lidocaine at causing vasoconstriction during ear surgery (Gessler et al, 2001). Anesthesia with epinephrine as additive is still required.…”
Section: Time (Min)mentioning
confidence: 99%
“…Additionally, epinephrine is often added to the local anesthetics to prolong the duration of central and peripheral neuraxial blockades (Scott et al, 1972), but it is important to limit the dosage of epinephrine seriously to prevent side effects. The optimal concentrations of epinephrine may vary based on the anesthetic agent and its injection site (Gessler et al, 2001;Liu et al, 1995;Scott et al, 1972). We presume that the addition of epinephrine may enhance and prolong propranolol cutaneous analgesia.…”
Section: Introductionmentioning
confidence: 99%